Motherhood and Shopping Behavior: The Gender-Based Balance Between Their Own Needs and Their Children's Needs (Third Sector Social Economic Review, 2025)
This study aims to understand how the identity of motherhood within the family structure is associated with contemporary consumption practices. In this qualitative study, semi-structured interviews were conducted with 12 mothers with children under the age of 12. The interviews were analyzed within the framework of the MEC (Means-End Chain) model; participant statements were coded and classified into themes in line with the feature-outcome-value chains. Eight main themes were identified in the study: Intensive motherhood and giving up individual consumption, development and health-oriented mindful consumption, seeking balance, seeking social approval, striving for independent parenthood, need-based shopping, digital influences and visibility. These themes show that motherhood is not only a caregiving activity, but also an emotional, economic and cultural responsibility undertaken within the family institution. The findings reveal that mothers put their children's needs at the center of their consumption decisions, while leaving their own individual needs in the background; this is often identified with the understanding of being a “good mother” and the desire to fulfill the ideal female role in the family. The study makes a methodological contribution to the literature by focusing on a value-based analysis of the relationship between motherhood and consumption with the MEC technique. It also suggests a critical perspective on representations of motherhood in marketing communication and the development of consumer policies that take into account women's emotional labor.
Keywords: Motherhood identity; Family and consumption; Gender roles; Family focused marketing; MEC analysis